REFINANCING IMPLEMENTATION IN PRO HAJJ PRODUCT FINANCING IN BANK PANIN DUBAI SYARIAH MALANG - Aisyah, Esy Nur; Putri, Qorina Lahadi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
DSN-MUI is an institution that handles issues related to the activities of financial institutions and has stipulated Fatwa Number 89/DSN-MUI/XII/2013 concerning Sharia Refinancing. This fatwa is stated in the OJK Circular Letter as a reference or guideline for implementing sharia refinancing products. This study aims to determine how to implement or apply Refinancing products in Pro Hajj financing at Bank Panin Dubai Syariah Malang. The research method uses a qualitative approach with data collection techniques using interviews, observation, and documentation. The results of the study found that Bank Panin Dubai Syariah Malang Branch applies Refinancing products to Hajj Financing using the Musyarakah Mutanaqisah contract or what is known as the MMQ contract. The contract used is by DSN-MUI Fatwa Number 89/DSN-MUI/XII/2013, which explains Refinancing. Bank Panin Dubai Syariah has fulfilled its obligations as an Islamic financial institution by applying Sharia principles. In implementing Refinancing product marketing at Panin Dubai Syariah Bank using the Telemarketing method, this method is used to attract customers. Using telephones and sending posters via WhatsApp can help banks market this product.